Heterozygosity decrease in wild boar mating system ‐ a case of outbreeding avoidance?. (8th December 2016) - Pérez‐González, J.; Costa, V.; Santos, P.; Carranza, J.; Zsolnai, A.; Fernández‐Llario, P.; Monteiro, N. M.; Anton, I.; Beja‐Pereira, A.
Abstract: In sexually reproducing organisms, the specific combinations of parental alleles can have important consequences on offspring viability and fitness. Accordingly, genetic relationship between mates can be used as a criterion for mate choice. Here, we used microsatellite genetic markers to estimate the genetic relationship between mating pairs in the wild boar, Sus scrofa . Males, females and foetuses proceeding from Portugal, Spain and Hungary were genotyped using 14 microsatellite markers. The genetic relationship between mates was estimated using different measures of foetus heterozygosity. We found that the observed heterozygosity of foetuses was lower than that expected under random mating. This result occurred mainly when Sd 2 (relatedness of parental genomes) was used as the heterozygosity measure. After simulations, we concluded that the observed low heterozygosity was possibly due to outbreeding avoidance. Outbreeding avoidance based on genetically different genomes might play an important role in species evolution and its genetic conservation. Abstract : In this work, foetus heterozygosity was used to estimate the genetic relationship between mates in wild boar from Portugal, Spain and Hungary. Foetus heterozygosity was lower than that expected under random mating. We propose outbreeding avoidance as the most likely process able to explain our results.